Serum albumin as predictor of post-operative morbidity and mortality - Sharma, Latika; Purohit, Poojan M.; Pipal, Dharmendra; Kothari, Saurabh; Srivastava, Harshit; Soni, Amit (International Surgery Journal, 2017)
Background: Protein energy malnutrition affects every organ system. So correct assessment of nutritional status is important as malnourishment is a risk factor for morbidity and morality in surgical patients. In our study, serum albumin has been taken as parameter for nutritional assessment. Methods: Study is conducted on 50 patients admitted in Department of General Surgery, Dr. Sampurnanand Medical College and associated Hospital, Jodhpur, Rajasthan, India for surgeries during January 2014-December 2015. Data was analyzed using Z-test and Fischer exact t-test and p value was calculated. P value <0.05 is considered statistically significant. Results: Patients with serum albumin <3gm/dl had more complications with maximum number of complications in age group of 41-60 year group. This finding was statistically significant. Conclusions: Low serum albumin patients has more post-operative complication than those with normal level and so is a good indicator of post-operative morbidity and mortality.